[HyEtPy]Cl–H2O: an efficient and versatile solvent system for the DABCO-catalyzed Morita–Baylis–Hillman reaction1. Issue 41 (7th May 2015) - Zhao, Sanhu; He, Meiyan; Guo, Zhaonan; Zhou, Na; Wang, Dou; Li, Jinlong; Zhang, Liwei
<x xml:space="preserve">Abstract</x> A very efficient and versatile solvent system, [HyEtPy]Cl–H2O, has been developed and used in the DABCO-catalyzed Morita–Baylis–Hillman reaction.